Decoupled Power Angle and Voltage Control of Electric Springs - Mok,KT; Tan,SC; Hui,SYR (IEEE Transactions on Power Electronics, 2015)
In this paper, a radial-chordal decomposition (RCD) technique is proposed to decouple the power angle and voltage control of a smart load based on the use of electric springs (ES). This RCD method is mathematically presented. A detailed comparison between the existing ES control schemes and the proposed RCD approach highlights its decoupling feature and merit on achieving multiple functionalities with a single ES. This RCD control method has been tested on a 2-kW small-scale power system. Simulation and experimental results confirmed that the power factor of the ES-integrated smart load can be improved by the chordal control while the mains voltage can be regulated by the radial control. It has also been demonstrated that the radial and chordal control can work simultaneously and independently.